Toxicological effects of benzo[a]pyrene on DNA methylation of whole genome in ICR mice - Zhao, L; Zhang, S; An, X; Tan, W; Pang, D; Ouyang, H (Cellular and Molecular Biology, 2015)
It has been well known that alterations in DNA methylation -an important regulator of gene transcription- lead to cancer. Therefore a change in the level of DNA methylation of whole genome has been considered as a biomarker of carcinogenesis. Previously, a large number of experimental results in genetic toxicology have showed that benzo[a]pyrene could cause DNA mutation and fragmentation. However, there was little to no studies on alterations in DNA methylation of genome directly result from exposure to benzo[a]pyrene. In this paper, possible mechanisms of alterations in whole genomic DNA methylation by benzo[a]pyrene were investigated using ICR mice after benzo[a]pyrene exposure. The blood, liver, pancreas, skin, lung and bladder of ICR mice were removed and checked after a fixed time interval (6 hours) of benzo[a]pyrene exposure, and whole genomic DNA methylation level was determined by high performance liquid chromatography (HPLC). The results exhibited tissue specificity, that is, the level of whole genomic DNA methylation decreases significantly in blood and liver, rather than pancreas, lung, skin and bladder of ICR mice. This study investigated the direct relationship between aberrant DNA methylation level and benzo[a]pyrene exposure, which might be helpful to clarify the toxicological mechanism of benzo[a]pyrene in epigenetic perspectives.